GAMIFICATION METHOD IN TEACHING AND LEARNING: A CASE OF RETAILING MANAGEMENT SUBJECT - Mohd Hafizie Suhaimi; Azyanee Luqman; Mohd Afifie Mohd Alwi; Md Zaki Muhamad Hasan; Afwan Hakim Md Mahdzir; Muhammad Naqib Mat Yunoh, (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
Currently, the use of gamification element in teaching and learning has become dominant. Generation Y students are more receptive to this technique as it is easier for them to grasp the information either inside or outside of the classrooms. With regards to this, a research on students’ engagement has been conducted in order to compare between traditional method and gamification method of teaching and learning among 150 students at a public university in the East Coast of Peninsular Malaysia. The result indicates that students’ engagement is higher when using gamification method. As a conclusion, the use of gamification element has been proven to increase the students’ interest in learning difficult subjects as well as improve the ability of lecturers to communicate information in a more efficient and effective manner.